Special water-based lubricating coolant for steel drum curling and its preparation method
Patent Information
- Application Number
- CN202611264689.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-20
AI Technical Summary
[0009]本发明的目的在于提供一种钢桶卷边专用水基润滑冷却剂及其制备方法,旨在解决现有通用水基加工液在150L及以下薄壁钢桶高速卷边工况中,低粘度配方雾化漂移与液膜承载难以兼得、高温蒸汽膜削弱冷却、镀锌层剥落粘模以及防锈与免清洗涂装兼容难以兼顾等问题
本发明提供了一种钢桶卷边专用水基润滑冷却剂,通过含氮硼酸酯、改性纳米氮化硼、改性聚氨酯缔合型增稠剂等组分的协同配伍,能够缓解150L及以下薄壁钢桶高速卷边中低粘度配方雾化漂移、液膜承载不足、高温蒸汽膜削弱冷却、镀锌层剥落粘模及防锈与涂装兼容难以兼顾等问题。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water-based lubricating coolant technology, specifically a water-based lubricating coolant for steel drum edge rolling and its preparation method. Background Technology
[0002] Steel drums are widely used metal containers in the industrial packaging field. Steel drum manufacturing involves multiple processes, including sheet metal cutting, rolling, welding, flanging, edge sealing, and surface coating. Among these, edge sealing is a crucial forming process that determines the sealing performance and structural integrity of the steel drum. During edge sealing, the flange of the drum body interlocks with the hook edge of the bottom (lid). The edge sealing rollers, rotating at high speed, continuously roll and press the interlocking area, causing both parts to undergo a complex plastic deformation process of "bending-folding-compacting," ultimately forming a mechanically interlocked sealing structure. In this process, the working surface of the edge sealing rollers and the workpiece material, as well as the interlocking metal layers, simultaneously endure high-pressure sliding friction and rolling pressure. The pressure in the contact area can reach hundreds of megapascals, and the local instantaneous temperature can exceed 200°C. These conditions determine that the edge sealing process is highly dependent on the performance of the lubricating and cooling media.
[0003] In recent years, with the continuous growth in demand for small and medium-sized packaging from industries such as fine chemicals, food additives, coatings, and pharmaceutical intermediates, the market share of steel drums with a capacity of 150L and below has gradually increased. Compared with 200L standard drums, the edge-rolling process of small and medium-sized steel drums presents more stringent technical characteristics: the thickness of the drum body is reduced from 0.8-1.2mm to 0.4-0.6mm, and lightweight products are even less than 0.35mm; the edge-rolling production line speed reaches 60-120 pieces / min; small and medium-sized drums are mostly used for packaging high-value-added contents, and the inner wall needs to be coated with food-grade or chemical-resistant coatings. The cycle between edge-rolling and inner and outer coating is tight, and offline cleaning stations and long-term drying and turnover conditions are usually not available. These characteristics make the performance requirements of lubricants and coolants for edge-rolling of small and medium-sized drums significantly different from those for 200L large drums, and edge-rolling lubrication solutions suitable for large drums cannot be directly transferred to the small and medium-sized drum scenario.
[0004] Meanwhile, replacing traditional oil-based and emulsion systems with water-based fully synthetic systems can reduce organic solvent cleaning processes and avoid the environmental burden of treating oily wastewater, making it a feasible technical path for the green manufacturing of small and medium-capacity thin-walled steel drums.
[0005] However, due to the constraints of narrow flange gaps, high contact pressures, instantaneous temperature rises, and the need for cleaning-free coating connections in small and medium-sized thin-walled steel drums, existing general-purpose water-based processing fluids face the following technical challenges in application, formation, and subsequent coating processes: Firstly, low-viscosity formulations struggle to simultaneously address both spraying and edge-curing lubrication. Steel drums of 150L and below, after edge-curing, form a multi-layered, interlocking structure with extremely narrow gaps between layers. The lubricant must possess low viscosity and high permeability to penetrate the interlayer interface and form a coating. During application, the edge-curing liquid is applied to the contact area between the roller and the drum body via high-pressure micro-spray. Lower liquid viscosity results in a higher proportion of fine mist and a wider aerosol diffusion range. These fine droplets, under the influence of airflow disturbances and roller rotation, drift to non-edge-curled areas such as the outer wall of the drum body and the inner surface of the lid. After drying, these droplets form spots or salt streaks, manifesting as pinholes or shrinkage defects with unpredictable locations and hidden causes during subsequent coating. Secondly, during the forming stage, the low-viscosity medium has a thin liquid film thickness and weak shear extrusion resistance in the contact area. Under high contact pressure and continuous roller friction, it is easily extruded from the contact area, leading to deterioration of the boundary lubrication state, manifesting as edge wrinkling, cracking, burrs, and uneven pressing.
[0006] Secondly, the high temperature during edge rolling and the peeling of the galvanized layer increase the difficulty of the process. The instantaneous temperature in the contact area of the edge rolling is high. Even when using a water-based medium, a vapor film may still appear in the contact area, blocking the heat exchange between the liquid film and the metal surface and weakening the cooling effect. At the same time, for galvanized steel drums, the galvanized layer is prone to cracking and peeling under high-pressure roller shearing during edge rolling. The peeled zinc powder forms a sticky mold after being repeatedly rolled on the roller surface, further damaging the surface quality of the edge rolling.
[0007] Thirdly, it's difficult to simultaneously address rust prevention and coating at the rolled edge. The rolled edge area of small and medium-capacity steel drums is formed by the flange of the drum body and the hook edge of the bottom (lid). The drum body and bottom (lid) are typically made of cold-rolled black steel sheet or galvanized steel sheet. Rolling the rolled edge can locally damage the original protective layer on the surface of the black steel sheet or the zinc coating and passivation film on the galvanized steel sheet, exposing the unprotected, fresh iron-based surface. The damaged area of the galvanized sheet is more prone to preferential corrosion due to the zinc-iron potential difference, resulting in white rust. During the short storage period before coating (24–72 hours), the exposed iron-based area is susceptible to rust. Since the rolled edge solution is usually supplied as a single, universal product for both galvanized and black steel drum production, the same formula needs to be effective in preventing rust on both materials. However, some rust-preventive components have a preferential adsorption tendency on the iron-based surface, resulting in insufficient coverage at the damaged zinc layer, easily leading to selective failure—"preventing iron but leaking zinc." To improve rust prevention, conventional water-based processing fluids usually contain inorganic salt rust inhibitors. However, these components tend to crystallize and precipitate after water evaporates, forming salt spots, which conflicts with the requirements of no-clean coating.
[0008] Therefore, developing a water-based fully synthetic edge-lubricating coolant that can improve the above-mentioned technical problems is of great significance for the manufacturing of thin-walled steel drums of 150L and below. Summary of the Invention
[0009] The purpose of this invention is to provide a water-based lubricating coolant and its preparation method specifically for steel drum edge rolling. This invention aims to solve the problems of existing general-purpose water-based processing fluids in high-speed edge rolling of thin-walled steel drums of 150L and below, such as the difficulty in achieving both low-viscosity formulation atomization drift and liquid film bearing capacity, weakened cooling due to high-temperature vapor film, peeling and sticking of zinc plating layer, and the difficulty in achieving both rust prevention and no-clean coating compatibility in high-speed edge rolling.
[0010] The objective of this invention is achieved through the following technical solution: A water-based lubricant and coolant specifically for steel drum edge rolling, comprising the following components in parts by weight: The mixture contains 4-8 parts of nitrogen-containing boron ester, 0.5-2 parts of modified nano boron nitride, 0.05-0.5 parts of modified polyurethane associative thickener, 10-17 parts of polyether, 2-4 parts of sodium molybdate-triethanolamine composite rust inhibitor, 0.1-0.3 parts of benzisothiazolinone, 0.1-0.3 parts of boric acid, and 60-85 parts of deionized water. The nitrogen-containing borate ester is obtained by the condensation reaction of boric acid, diethanolamine and polyethylene glycol; The modified boron nitride nanoparticles are obtained by surface modification of boron nitride nanoparticles with a co-hydrolysate of KH550 and polyethylene glycol silane; the polyethylene glycol silane is 3-(trimethoxysilyl)propyl polyethylene glycol with a molecular weight of 500-1000. The modified polyurethane associative thickener is obtained by an end-capping reaction of isocyanate-terminated polyurethane and polyethylene glycol monomethyl ether.
[0011] This invention provides a water-based lubricant and coolant specifically for steel drum edge rolling, which can alleviate the problems of existing general-purpose water-based processing fluids, such as the difficulty in achieving both narrow-gap penetration and controllable atomization, the difficulty in synchronizing high-temperature cooling and extreme-pressure lubrication, and the difficulty in coordinating rust prevention and coating compatibility. The specific functions of the components are as follows: In nitrogen-containing borate esters, the chelate ring structure containing BN coordination bonds formed by the condensation of boric acid and diethanolamine provides extreme pressure bearing capacity. Under high-pressure rolling friction conditions in the edge contact area, it forms a boundary lubricating film, reducing the incidence of edge wrinkling, cracking, and burrs. After being bridged by polyethylene glycol, the borate ester units are connected by PEG segments to form a polymeric structure. After drying, it forms a transparent film rather than a crystalline powder, reducing the white spots precipitated at the edge by conventional borate hydrolysis products. At the same time, the PEG segments, through hydrogen bonding and steric hindrance, inhibit the crystallization of sodium molybdate after water evaporation to a certain extent. Under conditions of thin residual liquid film and rapid drying, the rust-preventive components tend to be distributed in the edge area in a more uniform film form rather than in the form of large-particle crystals.
[0012] In modified nano-boron nitride, the nano-boron nitride has a high thermal conductivity. When dispersed in the edge-curling liquid, it can improve the thermal conductivity of the system, accelerate the heat dissipation in the edge-curling contact area, reduce the tendency of vapor film formation, and improve the cooling effect under high-temperature conditions. After surface modification with the co-hydrolysate of KH550 and polyethylene glycol silane, amino and PEG segments are introduced into the particle surface. The silanol produced after silane hydrolysis provides electrostatic repulsion, and the PEG segments provide steric hindrance. The two work together to keep the particles stably suspended in the formulation system containing anions such as sodium molybdate and boric acid, reducing the tendency of agglomeration and sedimentation. The amino groups on the particle surface can coordinate adsorb with the fresh metal surface and work synergistically with the boundary lubrication film formed by nitrogen-containing borate esters to reduce the direct shear and ploughing effect between metals in the edge-curling area. Thus, while reducing the mechanical peeling of the zinc plating layer, it indirectly reduces the tendency of zinc powder to transfer and adhere to the roller surface.
[0013] Under high shear rates at the nozzle, the modified polyurethane associative thickener exhibits typical high-shear thinning characteristics, with the hydrophobic associative network dissociating and the system viscosity decreasing. This prevents a significant increase in viscosity and does not affect nozzle atomization or narrow-gap penetration. Under low-shear conditions after the droplets leave the nozzle, the hydrophobic end groups associate and reform a weak network structure, inhibiting the breakup of the droplets into fine mist, increasing the average droplet size, and reducing aerosol drift and spot or salt streaks in non-edge-curling areas. End-capping with polyethylene glycol monomethyl ether improves the thickener's water solubility and dispersion uniformity, reducing the tendency to dry under intermittent spraying conditions and contributing to the stability of the spray application process. This thickener, added at low dosages, forms a weak associative network only under low-shear conditions after the droplets leave the nozzle, maintaining low viscosity overall under both static and high-shear conditions, ensuring penetration into narrow gaps.
[0014] In polyether systems, polyethylene glycol or ethylene oxide-propylene oxide copolyethers with molecular weights of 200–800 provide basic lubrication and liquid film maintenance capabilities; among them, low molecular weight polyethers with molecular weights of 200–300 have a fast resolution rate, which can reduce nozzle clogging under intermittent liquid supply conditions, while forming a molecular weight gradient with higher molecular weight polyethers, taking into account both narrow gap penetration and liquid film carrying capacity in the contact area.
[0015] In the sodium molybdate-triethanolamine composite rust inhibitor, sodium molybdate provides passivation protection for iron-based surfaces, while triethanolamine has a corrosion-inhibiting effect on zinc-based surfaces. When combined, the two have short-term rust prevention capabilities for the edge-damaged areas of cold-rolled black steel sheets and galvanized steel sheets, reducing the incidence of iron-based rust and galvanized white rust during storage before coating. Triethanolamine also acts as a pH adjusting component, working with boric acid to maintain the pH of the system at 8.0–9.0.
[0016] Benzisothiazolinone inhibits microbial growth during recycling and long-term storage, prevents the edge-curling liquid from becoming foul and deteriorating, and prevents biological slime from clogging the nozzles, thus maintaining a stable flow rate in the liquid supply system.
[0017] Boric acid and triethanolamine work synergistically to buffer and stabilize the pH of the system at 8.0–9.0, preventing pH fluctuations from exacerbating the hydrolysis of nitrogen-containing borate esters and further adversely affecting the effectiveness of the rust-preventive components.
[0018] In summary, the water-based lubricant and coolant obtained by the present invention through the synergistic formulation of its components can alleviate the contradictions between low viscosity penetration and controllable atomization, high temperature cooling and extreme pressure lubrication, and rust prevention and no-clean coating in the high-speed edge rolling of thin-walled steel drums of 150L and below. It is suitable for both galvanized steel sheet and black steel sheet, and does not require cleaning after edge rolling and does not affect the adhesion of subsequent internal / external coatings. It helps to reduce scrap rate and post-processing costs, and has engineering application potential for the green manufacturing of small and medium capacity thin-walled steel drums.
[0019] As some possible embodiments of this application, in the sodium molybdate-triethanolamine composite rust inhibitor, the mass ratio of sodium molybdate to triethanolamine is 1:1.5 to 3.
[0020] As some possible embodiments of this application, in the raw materials for preparing the nitrogen-containing borate ester, the molecular weight of polyethylene glycol is 200-400, the molar ratio of boric acid to diethanolamine is 1:0.8-1.2, and the molar ratio of polyethylene glycol to boric acid is 0.5-1:2.
[0021] As one of the possible implementation methods of this application, the preparation method of the nitrogen-containing borate ester is as follows: Boric acid and diethanolamine are mixed and reacted under toluene reflux for 2-3 hours to obtain a nitrogen-containing borate intermediate. After the reaction is completed, toluene is removed by vacuum distillation, followed by the addition of polyethylene glycol. The mixture is heated to 120-140°C under nitrogen protection and dehydrated under vacuum for 3-5 hours to obtain the final product.
[0022] As one of the possible implementation methods of this application, the preparation method of the modified boron nitride nanoparticles is as follows: KH550 and polyethylene glycol silane were mixed at a mass ratio of 1:0.5-1, and then added to an ethanol-water mixture in which the volume ratio of ethanol to water was 8:1-10:1. The pH was adjusted to 4-5, and the mixture was stirred at room temperature for 30-60 minutes to obtain a co-hydrolysate. Subsequently, nano-boron nitride was added, the temperature was raised to 60-70°C, and the mixture was stirred for 4-6 hours. After centrifugation, the mixture was washed with ethanol, vacuum dried, and then ground to depolymerize, thus obtaining the final product. The total amount of silane used is 3 to 8% of the mass of nano boron nitride.
[0023] As some possible embodiments of this application, the average particle size of the boron nanoparticles is 50-200 nm, the polyethylene glycol silane is 3-(trimethoxysilyl)propyl polyethylene glycol, and the molecular weight of the polyethylene glycol silane is 500-1000.
[0024] As one possible implementation method of this application, the preparation method of the modified polyurethane associative thickener is as follows: Isocyanate-terminated polyurethane is mixed with polyethylene glycol monomethyl ether at a molar ratio of 1:0.3-0.6, and the mixture is heated to 80-100°C under nitrogen protection and reacted for 3-5 hours to obtain the final product.
[0025] As one possible implementation method of this application, the isocyanate-terminated polyurethane is prepared by mixing polyethylene glycol (molecular weight 1000-2000) with dicyclohexylmethane diisocyanate at a molar ratio of 1:2-2.5, heating to 70-80°C under nitrogen protection, reacting for 2-3 hours, then adding octadecyl alcohol for partial end-capping, the molar ratio of octadecyl alcohol to dicyclohexylmethane diisocyanate being 0.2-0.4:1, and continuing the reaction for 1-2 hours to obtain the isocyanate-terminated polyurethane with a molecular weight of 5000-10000.
[0026] As some possible embodiments of this application, the polyether is at least one of polyethylene glycol or ethylene oxide-propylene oxide copolyether with a molecular weight of 200 to 800, wherein the low molecular weight polyether with a molecular weight of 200 to 300 accounts for 30 to 50% of the total polyether.
[0027] As one possible implementation of this application, in the raw materials for preparing the nitrogen-containing borate ester, a portion of diethanolamine is replaced with N-methyldiethanolamine, and the molar ratio of diethanolamine to N-methyldiethanolamine is 3 to 1:1. In actual implementation, the nitrogen-containing borate ester is in a weakly alkaline environment of 40 to 50°C and pH 8.0 to 9.0 for a long time during the circulation of the edge-curing solution. Its BO bond has a slow tendency to hydrolyze, and the boric acid produced by hydrolysis gradually accumulates in the circulation tank, increasing the risk of boric acid white spots precipitated at the edge. In this scheme, after partially replacing diethanolamine with N-methyldiethanolamine, the methyl group on the nitrogen atom of N-methyldiethanolamine has an electron-donating effect, which can enhance the stability of the BN coordination bond. At the same time, the steric hindrance of the methyl group can prevent water molecules from approaching the BO bond, slowing down the hydrolysis rate of the nitrogen-containing borate ester during circulation, reducing the amount of boric acid accumulation, and helping to maintain the stability of the rust prevention and cleaning-free performance of the edge-curing solution under long-term circulation conditions.
[0028] As some possible embodiments of this application, the end-capping agent of the modified polyurethane associative thickener is a mixture of polyethylene glycol monomethyl ether and terminal amino polyether, with a molar ratio of polyethylene glycol monomethyl ether to terminal amino polyether of 9:1 to 8:2, and the terminal amino polyether is a polyetheramine with a molecular weight of 800 to 1200. In actual implementation, during the recycling of the edge-curling liquid, the urethane bonds of the modified polyurethane associative thickener tend to slowly hydrolyze in a weakly alkaline environment of pH 8.0 to 9.0. After hydrolysis, the hydrophobic association ability of the thickener decreases, and the mist control effect decays with the usage time. In this solution, after partially replacing polyethylene glycol monomethyl ether with terminal amino polyether, the terminal amino polyether reacts with isocyanate to form urea bonds. The hydrolytic stability of urea bonds is better than that of urethane bonds, which can reduce the hydrolysis rate of the thickener during recycling, delay the decay of the mist control effect, and at the same time, the presence of a small amount of urea bonds does not affect the hydrophobic association performance of the thickener, which helps to maintain the long-term stability of the spray application process.
[0029] Furthermore, to achieve the above objectives, the present invention also provides a method for preparing a water-based lubricating coolant specifically for steel drum edge rolling, comprising the following steps: S1. Modified boron nitride nanoparticles were added to a portion of deionized water and ultrasonically dispersed to obtain a nano-dispersion. S2. Heat the remaining deionized water to 40-50°C, and add polyether, sodium molybdate-triethanolamine composite rust inhibitor, benzisothiazolinone and boric acid in sequence while stirring, and stir until fully dissolved. S3. Add the nitrogen-containing borate ester to the system obtained in step S2 and stir until fully dispersed and uniform; S4. Add the nano-dispersion obtained in step S1 to the system obtained in step S3 and disperse it by ultrasonication; S5. Add the modified polyurethane associative thickener to the system obtained in step S4, stir until uniform, and adjust the pH value to 8.0-9.0 with triethanolamine to obtain the final product.
[0030] In the above preparation method, the modified nano-boron nitride is first ultrasonically dispersed separately in a portion of deionized water. This allows it to undergo depolymerization and thorough wetting before contacting the full formulation system containing anions such as sodium molybdate and boric acid. This helps the particles maintain their dispersed state during subsequent mixing and reduces the risk of agglomeration. Subsequently, the polyether, composite rust inhibitor, antibacterial agent, and boric acid are dissolved at 40–50°C. This temperature range accelerates the dissolution of water-soluble additives while avoiding the risk of premature hydrolysis of the nitrogen-containing borate ester due to high temperatures, and does not adversely affect the stability of the nitrogen-containing borate ester. Adding the nitrogen-containing borate ester after the aqueous components are completely dissolved avoids excessively high local concentrations and uneven dispersion in a high-concentration environment with multiple components. Finally, a modified polyurethane associative thickener is added and the pH is adjusted. Introducing the thickener after all components are uniformly mixed helps establish a uniform hydrophobic associative network in the final formulation, avoiding localized uneven association caused by premature addition.
[0031] As some possible implementations of this application, in step S1, the ultrasonic frequency is 20-40 kHz; in step S2, the stirring speed is 300-500 r / min; and in step S3, the stirring speed is 200-400 r / min.
[0032] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a water-based lubricant and coolant specifically for steel drum edge rolling. Through the synergistic formulation of components such as nitrogen borate ester, modified nano boron nitride, and modified polyurethane associative thickener, it can alleviate problems such as atomization drift, insufficient liquid film bearing capacity, weakened cooling by high-temperature vapor film, peeling and sticking of zinc plating layer, and difficulty in achieving both rust prevention and coating compatibility in high-speed edge rolling of thin-walled steel drums of 150L and below.
[0033] Testing showed that the viscosity of the water-based lubricating coolant of this invention is in the range of 5–8 mPa·s, which meets the requirements for penetration into narrow gaps in thin-walled small barrels; droplet D 50 The coolant exhibits excellent performance in spray application, with a fine mist concentration of ≥31μm, a fine mist ratio of ≤7.0%, and a drift deposition rate of ≤4.6mg, indicating that fine mist generation and drift contamination are effectively controlled. A PB value of ≥775N, an edge wrinkling rate of ≤0.4%, a cracking rate of 0%, and a burr defect rate of ≤0.67%, demonstrating high extreme pressure bearing capacity and stable forming quality in the edge contact area. An edge temperature drop of ≥82℃ indicates good high-temperature cooling effect, effectively reducing the tendency for vapor film formation. A zinc layer peeling area ratio of ≤2.8% and roller zinc adhesion of grade 0 indicate good protection for the galvanized layer. Both black steel plates and galvanized plates achieve grade A rust prevention after 72 hours, and coating adhesion is grade 0 or 1, indicating good compatibility between short-term rust prevention and no-clean coating.
[0034] In summary, the water-based lubricant and coolant obtained by the present invention through the synergistic formulation of its components can take into account low viscosity penetration and controllable atomization, extreme pressure lubrication and high temperature cooling, bimetallic rust prevention and no-clean coating compatibility, and is suitable for both galvanized steel sheet and black steel sheet. It does not require cleaning after edge rolling and does not affect the adhesion of subsequent internal / external coatings. It has engineering application potential for the green manufacturing of thin-walled steel drums of 150L and below. Detailed Implementation
[0035] Example 1 1. Preparation of non-commercially available components (1) Preparation of nitrogen-containing borate ester: Boric acid and diethanolamine were added to the reactor in a molar ratio of 1:1. Toluene was added as a dehydrating agent, and the amount of toluene was 80% of the total mass of boric acid and diethanolamine. The reaction was carried out at 110°C for 2.5 h under toluene reflux to obtain the nitrogen-containing borate ester intermediate. After the reaction was completed, the toluene was removed by vacuum distillation. Polyethylene glycol (molecular weight 300) was added to the above intermediate at a molar ratio of polyethylene glycol to boric acid of 0.75:2. The temperature was raised to 130°C under nitrogen protection, and the dehydration reaction was carried out under reduced pressure for 4 h (vacuum degree -0.085 MPa, stirring speed 300 r / min). The mixture was cooled to room temperature to obtain the nitrogen-containing borate ester.
[0036] (2) Preparation of modified boron nitride nanoparticles: KH550 and 3-(trimethoxysilyl)propyl polyethylene glycol (molecular weight 750) were mixed at a mass ratio of 1:0.75 and added to an ethanol-water mixture (volume ratio of ethanol to water 9:1). The solid-liquid ratio of the silane mixture to the ethanol-water mixture was 1g:10mL. The pH was adjusted to 4.5 and stirred at room temperature for 45min to obtain a co-hydrolysate. Boron nitride nanoparticles with an average particle size of 100nm (particle size distribution D90≤500nm) were added to the co-hydrolysate system. The total amount of silane used was 5% of the mass of boron nitride nanoparticles. The temperature was raised to 65℃ and stirred for 5h (stirring speed 250 r / min). The mixture was centrifuged (4000 r / min, 10min), washed 3 times with ethanol, dried under vacuum at 60℃ for 6h, and ground and depolymerized to obtain modified boron nitride nanoparticles.
[0037] (3) Preparation of modified polyurethane associative thickener: Preparation of isocyanate-terminated polyurethane: Polyethylene glycol (molecular weight 1500) and dicyclohexylmethane diisocyanate were mixed at a molar ratio of 1:2.2, heated to 75°C under nitrogen protection, and reacted for 2.5 h (stirring speed 200 r / min). Then, octadecyl alcohol was added for partial end-capping. The molar ratio of octadecyl alcohol to dicyclohexylmethane diisocyanate was 0.3:1. The reaction was continued for another 1.5 h to obtain isocyanate-terminated polyurethane.
[0038] The above isocyanate-terminated polyurethane was mixed with polyethylene glycol monomethyl ether (molecular weight 450) at a molar ratio of 1:0.45, heated to 90°C under nitrogen protection, reacted for 4 hours (stirring speed 200 r / min), and cooled to room temperature to obtain the modified polyurethane associative thickener.
[0039] 2. Preparation of water-based lubricating coolant S1. Add 1 part of modified boron nitride nanoparticles to 20 parts of deionized water and ultrasonically disperse for 20 min (ultrasonic frequency 30 kHz) to obtain a nano-dispersion. S2. Heat 55.2 parts of deionized water to 45°C, and under stirring conditions (stirring speed 400 r / min), add 14 parts of polyether (including 5.6 parts of low molecular weight polyethylene glycol with a molecular weight of 250 and 8.4 parts of polyethylene glycol with a molecular weight of 600), 3 parts of sodium molybdate-triethanolamine composite rust inhibitor (including 1 part of sodium molybdate and 2 parts of triethanolamine), 0.2 parts of benzisothiazolinone and 0.2 parts of boric acid, and stir until fully dissolved; S3. Add 6 parts of nitrogen-containing borate ester to the system obtained in step S2 and stir for 45 min (stirring speed 300 r / min) until fully dispersed and uniform; S4. Add the nano-dispersion obtained in step S1 to the system obtained in step S3 and ultrasonically disperse for 20 min (ultrasonic frequency 30 kHz). S5. Add 0.2 parts of modified polyurethane associative thickener to the system obtained in step S4, stir until uniform (stirring speed 300 r / min), and adjust the pH value to 8.5 with triethanolamine to obtain the final product.
[0040] Example 2 Compared to Example 1, only some parameters were adjusted, while the remaining components and steps were the same as in Example 1. The specific adjustments are as follows: (1) In the preparation of nitrogen-containing borate esters, the molar ratio of boric acid to diethanolamine is 1:0.8, the molar ratio of polyethylene glycol to boric acid is 0.5:2, the reaction time of the first stage is 2h, and the reaction time of the second stage is 3h. (2) In the preparation of modified boron nitride nanoparticles, the mass ratio of KH550 to 3-(trimethoxysilyl)propyl polyethylene glycol is 1:0.5, the total amount of silane used is 3% of the mass of boron nitride nanoparticles, the solid-liquid ratio is 1g:10mL, and the reaction time is 4h. (3) In the preparation of modified polyurethane associative thickener, the molar ratio of isocyanate-terminated polyurethane to polyethylene glycol monomethyl ether is 1:0.3, and the reaction time is 3h; (4) In the preparation of water-based lubricating coolant, S1 is to add 2 parts of modified nano boron nitride and 20 parts of deionized water and ultrasonically disperse for 15 min; S2 is to add 53.8 parts of deionized water, 17 parts of polyether (including 5.1 parts of low molecular weight polyethylene glycol and 11.9 parts of polyethylene glycol with a molecular weight of 600), 2 parts of sodium molybdate-triethanolamine composite rust inhibitor (including 0.8 parts of sodium molybdate and 1.2 parts of triethanolamine), 0.1 parts of benzisothiazolinone and 0.3 parts of boric acid and stir at 300 r / min; S3 is to add 4 parts of nitrogen-containing borate ester and stir for 30 min at 200 r / min; S4 is to ultrasonically disperse for 15 min; S5 is to add 0.3 parts of modified polyurethane associative thickener and adjust the pH value to 8.0.
[0041] Example 3 Compared to Example 1, only some parameters were adjusted, while the remaining components and steps were the same as in Example 1. The specific adjustments are as follows: (1) In the preparation of nitrogen-containing borate esters, the molar ratio of boric acid to diethanolamine is 1:1.2, the molar ratio of polyethylene glycol to boric acid is 1:2, the reaction time of the first stage is 3h, and the reaction time of the second stage is 5h. (2) In the preparation of modified boron nitride nanoparticles, the mass ratio of KH550 to 3-(trimethoxysilyl)propyl polyethylene glycol is 1:1, the total amount of silane used is 8% of the mass of boron nitride nanoparticles, the solid-liquid ratio is 1g:20mL, and the reaction time is 6h. (3) In the preparation of modified polyurethane associative thickener, the molar ratio of isocyanate-terminated polyurethane to polyethylene glycol monomethyl ether is 1:0.6, and the reaction time is 5h; (4) In the preparation of water-based lubricating coolant, S1 is added with 0.5 parts of modified nano boron nitride and 20 parts of deionized water, and ultrasonically dispersed for 30 min; S2 is added with 56.65 parts of deionized water, 10 parts of polyether (including 5 parts of low molecular weight polyethylene glycol and 5 parts of polyethylene glycol with a molecular weight of 600), 4 parts of sodium molybdate-triethanolamine composite rust inhibitor (including 1 part of sodium molybdate and 3 parts of triethanolamine), 0.3 parts of benzisothiazolinone and 0.1 parts of boric acid, and stirred at a speed of 500 r / min; S3 is added with 8 parts of nitrogen-containing borate ester, and stirred for 60 min at a stirring speed of 400 r / min; S4 is ultrasonically dispersed for 30 min; S5 is added with 0.05 parts of modified polyurethane associative thickener, and the pH value is adjusted to 9.0.
[0042] Example 4 The only difference from Example 1 is that in the preparation of the nitrogen-containing borate ester, diethanolamine is partially replaced with N-methyldiethanolamine, and the molar ratio of diethanolamine to N-methyldiethanolamine is 2:1. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0043] Example 5 The only difference from Example 1 is that in the preparation of the modified polyurethane associative thickener, the capping agent is a mixture of polyethylene glycol monomethyl ether and amino-terminated polyether, with a molar ratio of polyethylene glycol monomethyl ether to amino-terminated polyether of 8.5:1.5, and the amino-terminated polyether is a polyetheramine with a molecular weight of 1000. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0044] Comparative Example 1 The only difference from Example 1 is that in the preparation of modified boron nanonitride, only KH550 is used for modification, and 3-(trimethoxysilyl)propyl polyethylene glycol is not added. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0045] Comparative Example 2 The only difference from Example 1 is that the modified polyurethane associative thickener is replaced with an equal amount of uncapped polyethylene glycol monomethyl ether isocyanate-terminated polyurethane (molecular weight 7500). The remaining components, amounts, and preparation steps are the same as in Example 1.
[0046] Comparative Example 3 The only difference from Example 1 is that the nitrogen-containing borate ester is replaced with an equal amount of uncondensed diethanolamine borate. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0047] Comparative Example 4 The only difference from Example 1 is that the nitrogen-containing borate ester is replaced with an equal amount of commercially available triethanolamine borate. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0048] Comparative Example 5 The only difference from Example 1 is that the modified boron nanonitride is replaced with an equal amount of unmodified boron nanonitride. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0049] Comparative Example 6 The only difference from Example 1 is that the modified polyurethane associative thickener is replaced with an equal amount of hydroxyethyl cellulose. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0050] Comparative Example 7 The only difference from Example 1 is that the separate dispersion step S1 is omitted, and the modified boron nanoparticles are directly added to the system obtained in S2. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0051] Comparative Example 8 The only difference from Example 1 is that only sodium molybdate is used in the composite rust inhibitor, without the addition of triethanolamine, and the amount of sodium molybdate used is 3 parts. The remaining components, amounts, and preparation steps are the same as in Example 1.
[0052] Experimental Example To verify the comprehensive effects of the water-based lubricant and coolant for steel drum edge rolling of this invention in terms of low viscosity mist control, extreme pressure lubrication, high temperature cooling, galvanized layer protection, rust prevention and coating compatibility, and cycle stability, performance tests were conducted on Examples 1-5 (denoted as S1-S5) and Comparative Examples 1-8 (denoted as D1-D8). Specifically, S1-S5 and D1-D6 participated in basic performance experiments (viscosity, pH, atomization, extreme pressure, cooling); S1-S5, D3, D4, and D8 participated in application performance experiments (edge rolling, galvanized layer protection, rust prevention, coating); and S1-S5, D1, D2, D3, D4, D7, and D8 participated in cycle stability experiments. All experiments were repeated three times in parallel, with a relative standard deviation (RSD) ≤ 5%, and the average value was taken as the final result. Specific test indicators and experiments are as follows: (1) Basic physical property test: The dynamic viscosity (mPa·s) and pH value of each sample were measured at 25℃.
[0053] (2) Atomized particle size and drift deposition amount test: Using a laser particle size analyzer, under spray pressure of 0.4 MPa and nozzle orifice diameter of 0.3 mm, the volume average particle size (D50) and fine mist ratio (volume percentage of droplets with a particle size <10 μm) of each sample after atomization were measured.
[0054] Drift deposition amount: Place a 200mm×200mm cold-rolled steel plate receiving plate at a distance of 20cm from the nozzle, at a 45° angle to the spray direction. After spraying for 5 seconds, dry at 60℃ for 30 minutes and weigh the increase in weight of the receiving plate, which is the drift deposition amount (mg).
[0055] (3) Extreme pressure lubrication performance test: The maximum non-seizure load (PB value) and sintering load (PD value) were determined using a four-ball friction tester. The steel balls were GCr15 bearing steel balls with a diameter of 12.7 mm. Test conditions: rotation speed 1450 r / min, room temperature, loading time 10s.
[0056] (4) Edge forming quality test: On the steel drum edge forming test machine, 500 18L steel drums made of 0.5mm thick cold-rolled steel plate and 0.5mm thick galvanized steel plate were continuously edged at an edge forming speed of 80 drums / min. The number of wrinkled drums, cracked drums, and burr-deficient drums were counted. Judgment criteria: Wrinkling is defined as the appearance of visually visible wavy or fish-scale wrinkles on the outer surface of the edge; cracking is defined as the appearance of visually visible cracks at the outer bend of the edge, and the crack length is ≥3mm; burr-deficient is defined as the appearance of visually visible metal burrs (length ≥1mm) on the edge of the edge or continuous axial scratches (length ≥5mm) on the inner wall of the flange. Wrinkling rate = number of wrinkled drums / 500 × 100%; Cracking rate = number of cracked drums / 500 × 100%; Burr-deficient rate = number of burr-deficient drums / 500 × 100%. The above experiment was repeated three times in parallel, and the arithmetic mean of the percentages obtained from the three trials was taken as the final result.
[0057] (5) Cooling performance test: In the edge-rolling simulation test, thermocouples were placed 5 mm from the outer edge of the contact area between the edge-rolling roller and the barrel body, and the highest temperature during the edge-rolling process was continuously recorded. Using the highest temperature T0 of dry edge-rolling (without any lubricant) as a benchmark, the temperature drop during edge-rolling of each sample was calculated: Temperature drop (°C) = T0 Sample T. In this experiment, T0 = 218℃.
[0058] (6) Zinc coating protection test: After the edge rolling simulation test, take the edge rolling sample of galvanized steel plate steel drum and cut 4 edge rolling section samples at equal intervals along the circumference. First, visually observe the continuity of the zinc coating at the outer rounded corner of the edge rolling under natural light. If necessary, use a 20x magnifying glass or low-magnification optical microscope to confirm. The zinc coating peeling area ratio is estimated by covering the 4 sections with transparent grid paper. The arithmetic mean is taken as the zinc coating peeling area ratio of the sample to characterize the overall integrity of the zinc coating. At the same time, check the zinc adhesion degree on the surface of the edge rolling roller and evaluate it according to 0 to 3 (0: no visible zinc adhesion; 1: slight zinc adhesion; 2: obvious zinc adhesion; 3: severe zinc adhesion, and scratches appear on the edge rolling surface).
[0059] (7) Rust prevention test: Each sample was coated onto the surface of 50mm×50mm cold-rolled black steel sheet and galvanized steel sheet test pieces, with a coating amount of 0.5mL / piece. After drying at 60℃ for 30min, the samples were placed in a constant temperature and humidity chamber (temperature 35℃, relative humidity 95%) for 72h. After removal, the surface of the test pieces was gently wiped with degreased cotton soaked in deionized water to remove water-soluble residues and dry matter, simulating simple surface treatment before coating. This wiping operation is only used to remove free water film and trace amounts of soluble residues on the surface during rating, so as to accurately observe whether the substrate has corroded; in the actual no-clean coating process, this wiping step is not necessary. Rating Criteria: Grade A (No Base Corrosion): Visual inspection reveals no red rust, yellow rust, or black corrosion spots on the test piece surface; slight watermarks, dried marks, or very slight interference colors due to moisture evaporation are permissible and can be wiped away; for galvanized sheets, very slight white haze that can be wiped away is permissible, but after wiping, a complete zinc layer is exposed, with no black substrate exposed. Grade B (Minor Rust): Scattered rust spots less than 1mm in diameter, not exceeding 5, or rust area less than 5%. Grade C (Local Rust): Rust area 5%–20%. Grade D (Severe Rust): Rust area greater than 20%.
[0060] (8) Coating adhesion test: Each sample was coated on the surface of a cold-rolled black steel sheet, with a coating amount of 0.5 mL / sheet. It was dried at 60℃ for 30 min, then sprayed directly with epoxy phenolic resin coating (dry film thickness 15-20 μm) without cleaning. After curing according to the coating curing conditions (200℃ × 20 min), a cross-cut adhesion test was performed according to GB / T 9286, with a rating of 0-5. Rating explanation: Grade 0 represents a completely smooth cut edge with no peeling; Grade 1 represents a small amount of coating peeling at the cut intersection, but the affected area does not exceed 5%. In the no-clean process for edge rolling of the steel drum, both Grade 0 and Grade 1 are considered to meet the compatibility requirements for subsequent coating adhesion.
[0061] (9) Cyclic Use Stability Test: Each sample was placed in a sealed container and continuously stirred at 50℃, pH 8.5, and a stirring speed of 200 r / min to simulate cyclic use conditions. Water was replenished weekly to maintain the liquid level, and a small amount of triethanolamine was added to maintain the pH at 8.0–9.0 to simulate on-site replenishment conditions. Samples were taken daily, filtered through a 0.45 μm filter membrane, and the concentration of free borate in the circulating liquid was measured (ion chromatography, mg / L). The proportion of fine mist was measured weekly, and the recovery rate of the fine mist proportion (%) was calculated. A 72-hour rust prevention test was conducted weekly on the circulating liquid. The test was conducted continuously for 4 weeks.
[0062] The test results are shown in Tables 1 to 3, and are detailed below: Table 1 Basic performance test results Table 2 Application performance test results Table 3. Cyclic stability test results (4 weeks) It is worth noting that "-" in Tables 1-3 indicates that the item was not tested. The reason is that the corresponding sample has already shown significant performance degradation in the relevant tested items, so there is no need to conduct further testing on other unrelated or less relevant items.
[0063] From Tables 1 to 3, we can see that: Examples 1-3, through the synergistic effect of components such as nitrogen-containing borate ester, modified nano boron nitride, and modified polyurethane associative thickener, can alleviate problems such as atomization drift of low viscosity formulations, insufficient liquid film bearing capacity, weakened cooling by high-temperature vapor film, peeling and sticking of zinc plating layer, and difficulty in achieving both rust prevention and coating compatibility in high-speed edge rolling of thin-walled steel drums of 150L and below.
[0064] Tests showed that the viscosities of Examples 1-3 were all within the range of 5-8 mPa·s, meeting the requirements for low viscosity penetration; droplet D 50The coolant exhibits excellent performance in spray application, with a fine mist concentration of ≥31μm, a fine mist ratio of ≤7.0%, and a drift deposition rate of ≤4.6mg, indicating that fine mist generation and drift contamination are effectively controlled. A PB value of ≥775N, an edge wrinkling rate of ≤0.4%, a cracking rate of 0%, and a burr defect rate of ≤0.67%, demonstrating high extreme pressure bearing capacity and stable forming quality in the edge contact area. An edge temperature drop of ≥82℃ indicates good high-temperature cooling effect, effectively reducing the tendency for vapor film formation. A zinc layer peeling area ratio of ≤2.8% and roller zinc adhesion of grade 0 indicate good protection for the galvanized layer. Both black steel plates and galvanized plates achieve grade A rust prevention after 72 hours, and coating adhesion is grade 0 or 1, indicating good compatibility between short-term rust prevention and no-clean coating.
[0065] In Example 4, after partially replacing diethanolamine with N-methyldiethanolamine, the cumulative amount of boric acid after 4 cycles was lower than that in Example 1, indicating that the hydrolytic stability of nitrogen-containing borate esters during the recycling process was improved, which helps to maintain the stability of the anti-rust and cleaning-free performance of the crimping solution under long-term recycling conditions.
[0066] In Example 5, after the introduction of end-capped amino polyether and polyethylene glycol monomethyl ether, the increase in the proportion of fine mist after 4 cycles was smaller than that in Example 1, indicating that the modified polyurethane associative thickener has improved the mist control durability during the cycle and helps to maintain the long-term stability of the spray application process.
[0067] In Comparative Example 1, only KH550 was used to modify the nano boron nitride, and 3-(trimethoxysilyl)propyl polyethylene glycol was not used for co-modification. The steric hindrance of the particles in the anionic formulation system was insufficient, and they gradually agglomerated during the recycling process. The proportion of fine mist increased more than in Example 1, indicating that the two-component modification of the co-hydrolysate is necessary to maintain the dispersion stability of the particles and the persistence of mist control.
[0068] In Comparative Example 2, the thickener was not capped with polyethylene glycol monomethyl ether, and its initial mist control capability was insufficient. The proportion of fine mist and the amount of drift deposition were both higher than in Example 1. After cycling, the recovery rate of fine mist increased, indicating that capping plays a key role in the water solubility and mist control stability of the thickener under intermittent spraying conditions.
[0069] In Comparative Example 3, the nitrogen-containing borate ester without polyethylene glycol bridging resulted in a decrease in extreme pressure bearing capacity, an increase in the rate of edge wrinkling, cracking, and burr defects, an increase in the proportion of zinc layer peeling area, zinc adhesion on the rollers, and a higher accumulation of boric acid after cycling. This indicates that polyethylene glycol bridging plays an important role in extreme pressure bearing capacity, edge forming quality, zinc layer protection, and hydrolytic stability.
[0070] In Comparative Example 4, commercially available triethanolamine borate was used to replace polyethylene glycol-bridged nitrogen-containing borate esters. The extreme pressure performance and edge-forming quality were worse than those of Example 1, and the cumulative amount of boric acid after cycling was higher than that of Example 1. This indicates that commercially available conventional nitrogen-containing borate esters cannot achieve the comprehensive performance of the modified product of this invention.
[0071] In Comparative Example 5, unmodified nano-boron nitride was used. Its dispersion stability in the formulation was poor, and the edge curling temperature was lower than that in Example 1. This indicates that the thermal conductivity of boron nitride can only be effectively utilized after surface modification with KH550 and 3-(trimethoxysilyl)propyl polyethylene glycol co-hydrolysate.
[0072] In Comparative Example 6, although the proportion of fine mist and the amount of drift deposition were lower when hydroxyethyl cellulose was used instead of the modified polyurethane associative thickener, the viscosity exceeded the low viscosity requirement of 5-8 mPa·s, which could not meet the process prerequisite of narrow-gap penetration in thin-walled small barrels, indicating that non-associative thickeners are not suitable for this scenario.
[0073] In Comparative Example 7, the S1 separate dispersion step was omitted, and the modified nano boron nitride was directly added to the whole formulation system. After cycling, the recovery of the fine mist was slightly higher than that in Example 1, indicating that separate ultrasonic dispersion is beneficial to the long-term suspension stability of the particles in the electrolyte system.
[0074] In Comparative Example 8, the composite rust inhibitor used only sodium molybdate and lacked triethanolamine. The short-term rust prevention level of both black steel plate and galvanized plate decreased, the coating adhesion deteriorated, and the rust prevention performance further deteriorated after cycling. This indicates that the sodium molybdate-triethanolamine composite is necessary for the compatibility of short-term rust prevention and no-clean coating of bimetallic materials.
Claims
1. A water-based lubricant and coolant specifically for steel drum edge rolling, characterized in that, Includes the following components by weight: The mixture contains 4-8 parts of nitrogen-containing boron ester, 0.5-2 parts of modified nano boron nitride, 0.05-0.5 parts of modified polyurethane associative thickener, 10-17 parts of polyether, 2-4 parts of sodium molybdate-triethanolamine composite rust inhibitor, 0.1-0.3 parts of benzisothiazolinone, 0.1-0.3 parts of boric acid, and 60-85 parts of deionized water. The nitrogen-containing borate ester is obtained by the condensation reaction of boric acid, diethanolamine and polyethylene glycol; The modified boron nitride nanoparticles are obtained by surface modification of boron nitride nanoparticles through a co-hydrolysate of KH550 and polyethylene glycol silane; The modified polyurethane associative thickener is obtained by an end-capping reaction of isocyanate-terminated polyurethane and polyethylene glycol monomethyl ether.
2. The water-based lubricating coolant for steel drum edge rolling according to claim 1, characterized in that, In the sodium molybdate-triethanolamine composite rust inhibitor, the mass ratio of sodium molybdate to triethanolamine is 1:1.5-3.
3. The water-based lubricant and coolant for steel drum edge rolling according to claim 1, characterized in that, In the raw materials for preparing the nitrogen-containing borate ester, the molecular weight of polyethylene glycol is 200-400, the molar ratio of boric acid to diethanolamine is 1:0.8-1.2, and the molar ratio of polyethylene glycol to boric acid is 0.5-1:
2.
4. The water-based lubricating coolant for steel drum edge rolling according to claim 3, characterized in that, The preparation method of the nitrogen-containing borate ester is as follows: Boric acid and diethanolamine are mixed and reacted under toluene reflux for 2-3 hours to obtain a nitrogen-containing borate intermediate. After the reaction is completed, toluene is removed by vacuum distillation, followed by the addition of polyethylene glycol. The mixture is heated to 120-140°C under nitrogen protection and dehydrated under vacuum for 3-5 hours to obtain the final product.
5. The water-based lubricant and coolant for steel drum edge rolling according to claim 1, characterized in that, The method for preparing the modified boron nitride nanoparticles is as follows: KH550 and polyethylene glycol silane were mixed at a mass ratio of 1:0.5-1, added to an ethanol-water mixture, and the pH was adjusted to 4-5. The mixture was stirred at room temperature for 30-60 min to obtain a co-hydrolysate. Then, boron nitride nanoparticles were added, the temperature was raised to 60-70℃, and the reaction was stirred for 4-6 h. The mixture was then centrifuged, washed with ethanol, vacuum dried, and ground to depolymerize to obtain the final product. The total amount of silane used is 3 to 8% of the mass of nano boron nitride.
6. The water-based lubricating coolant for steel drum edge rolling according to claim 1, characterized in that, The average particle size of the boron nitride nanoparticles is 50–200 nm, and the molecular weight of the polyethylene glycol silane is 500–1000.
7. The water-based lubricating coolant for steel drum edge rolling according to claim 1, characterized in that, The preparation method of the modified polyurethane associative thickener is as follows: Isocyanate-terminated polyurethane is mixed with polyethylene glycol monomethyl ether at a molar ratio of 1:0.3-0.6, and the mixture is heated to 80-100°C under nitrogen protection and reacted for 3-5 hours to obtain the final product.
8. The water-based lubricating coolant for steel drum edge rolling according to claim 1, characterized in that, The polyether is at least one of polyethylene glycol or ethylene oxide-propylene oxide copolyether with a molecular weight of 200 to 800, wherein the low molecular weight polyether with a molecular weight of 200 to 300 accounts for 30 to 50% of the total polyether.
9. A method for preparing a water-based lubricating coolant for steel drum edge rolling as described in any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Modified boron nitride nanoparticles were added to a portion of deionized water and ultrasonically dispersed to obtain a nano-dispersion. S2. Heat the remaining deionized water to 40-50°C, and add polyether, sodium molybdate-triethanolamine composite rust inhibitor, benzisothiazolinone and boric acid in sequence while stirring, and stir until completely dissolved. S3. Add the nitrogen-containing borate ester to the system obtained in step S2 and stir until it is completely dispersed and uniform; S4. Add the nano-dispersion obtained in step S1 to the system obtained in step S3 and disperse it by ultrasonication; S5. Add the modified polyurethane associative thickener to the system obtained in step S4, stir until uniform, and adjust the pH value to 8.0-9.0 with triethanolamine to obtain the final product.